Real-World Effectiveness of Inhalation Therapy Among Patients With Symptomatic COPD in China: A Multicenter Prospective Study - Cheng, Wei; Duan, Jiaxi; Zhou, Aiyuan; Zhao, Yiyang; Yi, Rong; Liu, Yi; Deng, Dingding; Li, Xin; Zeng, Yuqin; Peng, Yating; Song, Qing; Lin, Ling; et al. (Frontiers in Pharmacology, 2021)
Purpose: This real-world study evaluated the effectiveness of different inhalation therapies in patients with symptomatic chronic obstructive pulmonary disease (COPD) in China and also explored the relevant factors that influence the effectiveness of inhalation therapy. Patients and Methods: We conducted a multicenter prospective longitudinal study that was carried out in 12 hospitals in China from December 2016 to June 2021. A face-to-face interview was conducted to collect data. Baseline data were collected at the first visit. Minimum clinically important difference (MCID) was defined as attaining a COPD assessment test (CAT) decrease ≥2. We mainly assessed the MCID and the incidence of exacerbations at the 6-month follow-up. Results: In 695 patients, the mean age was 62.5±8.2 years, with a mean CAT score of 15.1±6.0. Overall, 341 (49.1%) patients attained the MCID of CAT and the incidence of exacerbation during follow-up was 22.3%. Females were significantly more likely to attain MCID than male in COPD patients (adjusted odd ratio (aOR)=1.93, adjusted 95% confidence interval (a95%CI)=1.09-3.42, P=0.024). Patients treated with LABA/LAMA or ICS/LABA/LAMA (ICS, inhaled corticosteroid; LABA, long-acting β2-agonist; LAMA, long-acting muscarinic antagonist) were more likely to attain MCID than patients treated with LAMA (aOR=3.97, a95%CI=2.48-6.35, P＜0.001; aOR=3.17, a95%CI=2.09-4.80, P＜0.001, respectively). Patients treated with LABA/LAMA had a higher incidence of severe exacerbation than patients treated with ICS/LABA/LAMA (aOR=1.95, a95%CI=1.04-3.66, P=0.038). Conclusion: The incidence of MCID in symptomatic COPD patients treated with inhalation therapy was nearly 50%. Patients treated with LABA/LAMA or ICS/LABA/LAMA were more likely to attain MCID than patients treated with LAMA. Patients treated with LABA/LAMA had a higher incidence of severe exacerbations than with ICS/LABA/LAMA.